Susceptibility of bacterial isolates from Turkey - A report from the Meropenem Yearly Susceptibility Test Information Collection (MYSTIC) Program - KORTEN, VOLKAN (TAYLOR & FRANCIS LTD, 2007)
The study monitored the susceptibility of nosocomial pathogens to meropenem and comparator antimicrobial agents isolated as part of the Meropenem Yearly Susceptibility Test Information Collection (MYSTIC) Program from Turkish university hospitals. In terms of minimum inhibitory concentration 90% (MIC90) values, meropenem was two- and eight-fold more active than imipenem against Escherichia coli and Klebsiella pneumoniae, respectively. 40.5% of K. pneumoniae, 23.1% of Klebsiella oxytoca and 15.3% of E. coli isolates were extended-spectrum P-lactamase (ESBL) producers. Piperacillin/tazobactam was the most active agent against isolates of Pseudomonas aeruginosa, followed by meropenem and imipenem. Against Acinetobacter baumannii isolates, meropenem and imipenem were the most active agents. Continued surveillance by the MYSTIC Program appears to be prudent to help focus on effective empiric treatment regimens.
Keywords: antimicrobial resistance; nosocomial infections; susceptibility surveillance; INTENSIVE-CARE UNITS; GRAM-NEGATIVE BACTERIA; ANTIMICROBIAL RESISTANCE; ANTIBIOTIC-RESISTANCE; CDC DEFINITIONS; BETA-LACTAMASES; 8 HOSPITALS; SURVEILLANCE; INFECTIONS; PREVALENCE